A calcium- and voltage-dependent chloride current in developing chick skeletal muscle. - Hume, R I (1989)
1. Depolarization of embryonic chick myotubes from negative potentials elicits a rapid spike followed by a long-duration after-potential. The ionic basis of the long-duration after-potential was examined by making intracellular recordings from cultured myotubes, and by making whole-cell patch-clamp recordings from myoblasts and myoballs. 2. The peak potential of the long-duration after-potential varied with the chloride gradient, suggesting that a conductance increase to chloride is involved in generating the after-potential. However, a calcium current was also implicated, since lowering the extracellular calcium or replacing extracellular calcium with cobalt abolished the after-potential. 3. When extracellular calcium was replaced with strontium or barium, short-duration spikes similar to calcium spikes were observed, but only strontium was able to support activation of long-duration after-potentials. Intracellular injection of calcium or strontium into myotubes bathed in calcium-free extracellular solutions restored the ability of depolarization to evoke an after-potential. Intracellular injection of magnesium, barium, nickel or cobalt did not restore this ability. These experiments strongly suggested that the long-duration after-potential was due to a calcium- and voltage-activated chloride current. 4. Whole-cell voltage-clamp recordings from myoballs and myoblasts showed that a large chloride conductance could be activated by depolarization when the internal free calcium concentration was buffered at levels greater than 10(-7) M. At 2.5 x 10(-7) M-calcium, the voltage dependence of activation was steepest in the range of -30 to -20 mV and the activation kinetics varied with the membrane potential. The time to half-maximal activation ranged from 0.1 s at positive potentials to greater than 1 s at more negative potentials. The time constant for deactivation was approximately 1 s at -50 mV. No inactivation was observed. 5. The selectivity of the chloride current was measured by substituting other anions for chloride. The following permeability series was found: I- greater than NO3- greater than Br- greater than Cl- greater than acetate greater than F- greater than SO4- = glucuronate. Thus anion permeability decreased as the hydration radius increased. 6. Measurements of the resting potential of developing myoblasts and myotubes under 'physiological' conditions (37 degrees C, bicarbonate buffer) suggest that the after-potential acts to depolarize these cells 10-20 mV above their resting potential (approximately -60 mV) for several seconds. 7. We discuss the possibility that the long-duration after-potential may be involved in triggering myoblast fusion and in the generation of bursts of spontaneous contractions in developing myotubes.